Comparison of differences in transcriptional and genetic profiles between intra-central nervous system and extra-central nervous system large B-cell lymphoma - Shu Wang; Hong Chen; Bo Dai; Kang Zheng; Jiajun Zheng; Yuqi Zhu; Yan Yuan; Tianling Ding; Qian Wang; Liqian Xie; Rui Feng; Fengping Zhu; et al. (Neoplasia: An International Journal for Oncology Research)
Primary central nervous system diffused large B-cell lymphoma (PCNS-DLBCL) is a rare type of non-Hodgkin lymphoma restricted to the central nervous system (CNS). To explore its specific pathogenesis and therapeutic targets, we performed multi-omics sequencing on tumor samples from patients diagnosed with PCNS-DLBCL, secondary CNS-DLBCL or extracranial (ec) DLBCL.By single-cell RNA sequencing, highly proliferated and dark zone (DZ)-related B cell subclusters, MKI67_B1, PTTG1_B2 and BTG1_B3, were predominant significantly in PCNS-DLBCL. Compared to SCNS-DLBCL and ecDLBCL, an immune-suppressive tumor microenvironment was observed in PCNS-DLBCL by analysis of immune-stimulating/inhibitory ligand‒receptor (L-R) pairs. By performing whole-exome sequencing in 93 patients, mutations enriched in BCR-NFkB and TLR pathways and the cooperation of these two pathways were found to be predominant in PCNS-DLBCL comparing to nonGCB-ecDLBCL. In summary, our study provides comprehensive insights into the transcriptomic and genetic characteristics of PCNS-DLBCL in contrast to ecDLBCL and will help dissect the oncogenic mechanism of this disease.